2017
DOI: 10.5152/tpd.2016.4911
|View full text |Cite
|
Sign up to set email alerts
|

Determination the Role of Rhipicephalus sanguineus for Transmission of Leishmania major to Reservoir Animals

Abstract: üzerinde beslenmesini takiben, doymuş larvalar ve uygun koşullarda gömlek değiştiren larvalardan elde edilen aç nimflerden oluşan toplam 65 kene havuzu oluşturulmuştur. Bu havuzlar polimeraz zincir reaksiyonu (PZR) ve gerçek zamanlı PZR (RT-PCR) testi ile L. major yönünden test edilmiştir. Bulgular: Enfekte edilerek, üzerine Rh. sanguineus larvası konulan gerbil, tüm kenelerin düşmesini takiben uyutulmuş ve nekropsisi gerçekleştirilmiştir. Yapılan incelemelerde, gerbilin tüm iç organ ve dokularında amastigotla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In a previous study under laboratory conditions, the PCR performed to detect Leishmania major in unfed Rhipicephalus sanguineus nymphs molted from larvae fed on infected Gerbils Meriones unguiculatus was negative (Bilgic et al 2017). To the best of our knowledge, Leishmania major is detected here in naturally infected ticks for the first time.…”
Section: Resultsmentioning
confidence: 51%
“…In a previous study under laboratory conditions, the PCR performed to detect Leishmania major in unfed Rhipicephalus sanguineus nymphs molted from larvae fed on infected Gerbils Meriones unguiculatus was negative (Bilgic et al 2017). To the best of our knowledge, Leishmania major is detected here in naturally infected ticks for the first time.…”
Section: Resultsmentioning
confidence: 51%
“…Meriones unguiculatus were examined by RT-PCR. The results showed that none of the pools was infected with L. major [33]. The study conducted in Turkey could yield more precise results if it used the main reservoirs related to study potency of ticks in the transmission of parasites.…”
Section: Discussionmentioning
confidence: 97%
“…In another study in Turkey, to investigate the presence of L. major , the pools of R. sanguineus ticks on Meriones unguiculatus Milne-Edwards, 1867 were examined by RT-PCR. The results showed that none of the pools was infected with L. major ( 36 ). However, in this study the main reservoir has not been tested for the potency of ticks in the transmission of L. major .…”
Section: Discussionmentioning
confidence: 99%